Exploring the Dual Apprenticeship Program in Benin Republic: Analyzing Opportunities and Overcoming Challenges - Odjo, Zinsou Cosme (Journal of Pedagogy and Education Science, 2024)
The purpose of this paper is to explore the current state of Benin’s dual apprenticeship program, specifically its opportunities and challenges, as well as potential solutions. Since 2003, the vast majority of Benin young people have been trained on the job in the work techniques of a given trade in the artisan workshop. This study used a mixed-methods approach to understand the effectiveness, efficiency, and sustainability of Benin’s dual apprenticeship program. Primary data was collected through online interviews, with secondary data from government documents, decrees, policies, and project progress reports. The study focused on the cities of Cotonou, Sèmè-Podji, Parakou, and Porto-Novo, with 63 purposefully selected participants. The collected data was analyzed using thematic and content analysis to identify key themes and patterns. The results show that the dual apprenticeship program provides apprentices with a three-year training program that combines practical experience in artisan workshops with theoretical training at vocational training centers (VTCs). Upon completion, apprentices receive the “Certificat de Qualification Professionnelle” (CQP). However, issues such as outdated entrance or recruitment processes, outdated training materials, insufficient student manuals, lack of trainer quality control, and failure to meet basic obligations hinder its success. Similarly, it is noted that the program only includes 13 out of 300 craft occupations, and trainees are placed in VTCs far from their homes. To this end, the program's expansion to other crafts and engaging all stakeholders in clearly defined responsibilities will lead to the program's effectiveness and sustainability in Benin Republic.